2016
DOI: 10.1097/ccm.0000000000001625
|View full text |Cite
|
Sign up to set email alerts
|

High Intracranial Pressure Induced Injury in the Healthy Rat Brain

Abstract: Objective We recently showed that increased intracranial pressure (ICP) to 50 mmHg in the healthy rat brain results in microvascular shunt (MVS) flow characterized by tissue hypoxia, edema and increased blood brain barrier permeability. We now determined whether increased ICP results in neuronal injury by Fluoro-Jade stain (FJS) and whether changes in cerebral blood flow (CBF) and cerebral metabolic rate for oxygen (CMRO2) suggest nonnutritive MVS flow. Design Intracranial pressure was elevated by a reservoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Together, these phenotypes are highly similar to the key findings of elevated ICP in humans (papilledema, ischemia, RGC thinning, functional deficit, optic nerve injury), and strongly suggest that this model can be used to study human diseases of elevated intracranial pressure such as IIH and SANS 12 14 . As inducible models of ICP elevation are otherwise lacking, this system is a major improvement over the few other current models of ICP elevation, which either lack the ability to refine ICP to desired parameters of level and duration or are acute in nature 16 18 , 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together, these phenotypes are highly similar to the key findings of elevated ICP in humans (papilledema, ischemia, RGC thinning, functional deficit, optic nerve injury), and strongly suggest that this model can be used to study human diseases of elevated intracranial pressure such as IIH and SANS 12 14 . As inducible models of ICP elevation are otherwise lacking, this system is a major improvement over the few other current models of ICP elevation, which either lack the ability to refine ICP to desired parameters of level and duration or are acute in nature 16 18 , 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Within this context, neuronal ischemia secondary to mechanical trauma and alterations to axoplasmic flow and optic nerve head vasculature is thought to be a key component 12 , 15 . To better understand these processes, there has been considerable interest in identifying animal models to assist in the study of IIH, papilledema, and elevated ICP 16 27 . Unfortunately, many of the existing disease models either do not allow for sustained ICP elevation in living animals, do not allow for customizable ICP elevation to levels at the discretion of the investigators, or cannot be performed in genetically tractable organisms such as mice.…”
Section: Introductionmentioning
confidence: 99%
“…Other limitations of the model are that CBF is derived without accounting for changes in cerebral metabolism, the effects of medications or CSF diversion on cerebrovascular dynamics, and the consequence of surgical interventions (e.g., craniotomy, hematoma evacuation). Neither does the model account for brain heterogeneity in CA and microvascular nonnutritive phenomena such as shunt flow ( 29 ). That said, there are four advantages of our in silico testing: 1) “ground truth” CA is known and model parameters can be set to desired values; 2) changes in BP and ICP can be controlled and examined; 3) confounding factors can be controlled or eliminated; and 4) measurement errors can be removed as noise level can be controlled.…”
Section: Discussionmentioning
confidence: 99%
“…To test that, several animal studies used increased ICP to decrease CPP instead of decreasing arterial pressure and reported loss of autoregulation at ~30 mmHg [2-5]. The reason for an “apparently” better preserved autoregulation at a lower CPP was unclear until we showed that in a normal rat brain high ICP-induced a transition of capillary blood flow to high velocity, non-nutritive microvascular shunt (MVS) flow that was associated with brain hypoxia, edema and blood brain barrier (BBB) damage [6-7]. This transition was correlated with loss of CBF autoregulation undetected by static autoregulatory curves but identified by induced dynamic ICP (iPRx) and cerebrovascular (iCVRx) reactivity [8].…”
Section: Introductionmentioning
confidence: 99%